Evaluasi dan Pengembangan Program Revitalisasi KUA sebagai Upaya Peningkatan Kualitas Layanan Masyarakat di Provinsi Nusa Tenggara Barat - Khoirul Alam, Abdul Haris (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2024)
This Policy Paper describes that public services at the Religious Affairs Office (KUA) have received a lot of corrections from the community in West Nusa Tenggara Province. About this, KUA services will be improved by using KUA revitalization. However, the implementation of KUA revitalization has many obstacles that cannot be resolved in a short time. The purpose of this analysis is to evaluate and develop the KUA revitalization program in West Nusa Tenggara Province. This analysis was carried out using a qualitative approach, and data analysis using a descriptive approach. The analysis results are: 1) The KUA revitalization program is not only an Islamic Guidance program but a comprehensive Ministry of Religious Affairs program. 2) KUA revitalization is not only a change in mindset and culture set but also an agent of change. 3) The main change in KUA revitalization is in changes in human resources. 4) Improvement of facilities and infrastructure is carried out based on the priority scale of KUA conditions. 5) It is necessary to make changes to the rules that are linear with the KUA revitalization program, especially the rules related to SBSN so that they can synergize to accelerate the progress of KUA revitalization. The conclusion is that the KUA revitalization program will be successful if there is cooperation between all work units within the Ministry of Religious Affairs.